1978
DOI: 10.1111/j.1399-3054.1978.tb02565.x
|View full text |Cite
|
Sign up to set email alerts
|

The After‐Effect of Water Stress on Chlorophyll Formation during Greening and the Levels of Abscisic Acid and Proline in Dark Grown Wheat Seedlings

Abstract: Cut seedlings of wheat plants {Triticum aestivum L, cv, Starke II Weibull) between 6 and 7 days old were water stressed in darkness by exposing them to air of 35% relative humidity 2,5 to 20 h. This treatment resulted in a water potential of -11 bars in the leaves after 20 h. The leaves were then rewatered and irradiated. The chlorophyll formation that took place in fully turgid leaves during the greening was markedly decreased in the case of the water-stress pretreatment, and especially the lag phase was prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
2
10
1
1
Order By: Relevance
“…Mg 2+ is an important element occupying a central position in the chlorophyll molecule, thereby affecting the concentration of chlorophylls a and b in the green plant tissues . In fact, the results of the present study revealed that the photosynthetic pigments contents were less than those reported for many glycophytes (Bengtson et al 1987;Alhadi et al 1999;Yasseen 2001). Na + and Cl − may interfere with the accumulation of macronutrients, by inhibiting H + -ATPase of plasma membranes and consequently inhibit the protein transporters leading to nutrient imbalance (Fukuda et al 1998).…”
Section: Resultscontrasting
confidence: 78%
“…Mg 2+ is an important element occupying a central position in the chlorophyll molecule, thereby affecting the concentration of chlorophylls a and b in the green plant tissues . In fact, the results of the present study revealed that the photosynthetic pigments contents were less than those reported for many glycophytes (Bengtson et al 1987;Alhadi et al 1999;Yasseen 2001). Na + and Cl − may interfere with the accumulation of macronutrients, by inhibiting H + -ATPase of plasma membranes and consequently inhibit the protein transporters leading to nutrient imbalance (Fukuda et al 1998).…”
Section: Resultscontrasting
confidence: 78%
“…The Pchlide with fluorescence emission at 655 nm is rapidly transformed to Chlide when the dark‐grown leaves are irradiated. Different stress conditions are known to decrease the fluorescence emission at 655 nm and increase the emission at 633 nm (Bengtson et al 1978, Le Lay et al 2001) leading to a reduced accumulation of chlorophyll (Bengtson et al 1978, Duysen and Freeman 1974). The inhibition of the chlorophyll accumulation after salt treatment could be expected to be dependent on a reduced content of Pchlide fluorescing at 655 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Small variations in the peak position of the long‐wavelength Pchlide form were found to be species dependent (Böddi et al 1992, Amirjani and Sundqvist 2006). Factors such as phytohormones, drought and leaf age influence the proportion between long‐wavelength and short‐wavelength Pchlide forms (Bengtson et al 1977, 1978, Schoefs and Franck 1993, Schoefs et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves which represent the major visible organs in the apical zone (82% of apical sample dry weight), may be mainly responsible for the ABA variations during the first week of culture [3] . Leaves which represent the major visible organs in the apical zone (82% of apical sample dry weight), may be mainly responsible for the ABA variations during the first week of culture [3] .…”
Section: Discussionmentioning
confidence: 99%